Silken prey ebook - Sandford, John (Lucas Davenport, 2013)
Murder. Scandal. Politics. And one billionaire heiress so dangerous in so many ways. An explosive Lucas Davenport thriller from #1 New York Times bestselling author John Sandford. All hell has broken loose in the capital. An influential state senator has been caught with something very, very nasty on his office computer. The governor can’t believe it—the senator’s way too smart for that, even if he is from the other party. Something’s not right. As Davenport investigates, the trail leads to a political fixer who has disappeared, then—troublingly—to the Minneapolis police department itself, and most unsettling of all, to a woman who could give Machiavelli lessons in manipulation. She has very definite ideas about the way the world should work—along with the money, ruthlessness, and cold-blooded will to make it happen.